2018
DOI: 10.1021/acs.jpclett.8b00300
|View full text |Cite
|
Sign up to set email alerts
|

What Controls the Limit of Supercooling and Superheating of Pinned Ice Surfaces?

Abstract: Cold-adapted organisms produce antifreeze proteins and glycoproteins to control the growth, melting and recrystallization of ice. It has been proposed that these molecules pin the crystal surface, creating a curvature that arrests the growth and melting of the crystal. Here we use thermodynamic modeling and molecular simulations to demonstrate that the curvature of the superheated or supercooled surface depends on the temperature and distances between ice-binding molecules, but not the details of their interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 68 publications
4
81
1
Order By: Relevance
“…Here, αp is a geometric constant (two for cylindrical ice cap, four for spherical), γ sl is the ice-liquid surface tension, Tm is the bulk freezing point, ν is the molar volume of ice, ∆Hm is the molar latent heat of fusion, θ is the ice cap contact angle, and d is distance between adsorbed AFPs. This theory has recently been supported via molecular simulation work by Naullage et al (9), who accurately calculated ∆T from θ and d for a model system. Additionally, Kuiper et al (10) confirmed that the binding of an AFP to the ice front is nearly irreversible in microsecond-long simulations, agreeing with earlier experimental evidence (11).…”
Section: ∆T = αPmentioning
confidence: 79%
See 2 more Smart Citations
“…Here, αp is a geometric constant (two for cylindrical ice cap, four for spherical), γ sl is the ice-liquid surface tension, Tm is the bulk freezing point, ν is the molar volume of ice, ∆Hm is the molar latent heat of fusion, θ is the ice cap contact angle, and d is distance between adsorbed AFPs. This theory has recently been supported via molecular simulation work by Naullage et al (9), who accurately calculated ∆T from θ and d for a model system. Additionally, Kuiper et al (10) confirmed that the binding of an AFP to the ice front is nearly irreversible in microsecond-long simulations, agreeing with earlier experimental evidence (11).…”
Section: ∆T = αPmentioning
confidence: 79%
“…Work by Naullage et al (9) suggests that bulkier AFPs should display increased ∆T . We, therefore, also tested the inclusion of the following variables: protein height, H ; distance across the binding plane, D; molecular mass of the protein, Mp; and radius of gyration, Rg .…”
Section: 28mentioning
confidence: 99%
See 1 more Smart Citation
“…The actual IRI seen, however, was rather weak requiring 5 mg mL −1 to inhibit 50% of ice growth. AFPs and AFGPs also show facial amphiphilicity and simulations suggest this facial amphiphilicity is crucial for AFGPs but not necessarily for AFPs . These experiments provided crucial data that a second structural feature, after ice binding, can be used to introduce IRI into a synthetic material; spatially segregated hydrophobic/hydrophilic domains, but without micellization.…”
Section: Facially Amphiphilic Non‐ice‐binding Materials and Compoundsmentioning
confidence: 90%
“…AFPs and AFGPs also show facial amphiphilicity [66,68] and simulations suggest this facial amphiphilicity is crucial for AFGPs [33] but not necessarily for AFPs. [58,69] These experiments provided crucial data that a second structural feature, after ice binding, can be used to introduce IRI into a synthetic material; spatially segregated hydrophobic/ hydrophilic domains, but without micellization. Mitchell et al further used self-assembling metallohelices to probe this concept.…”
Section: Facially Amphiphilic Non-ice-binding Materials and Compoundsmentioning
confidence: 99%